Freehand SPECT‐guided sentinel lymph node biopsy in early oral squamous cell carcinoma. Issue 11 (17th January 2014) - Bluemel, Christina; Herrmann, Ken; Müller–Richter, Urs; Lapa, Constantin; Higuchi, Takahiro; Wild, Vanessa; Buck, Andreas K.; Kübler, Alexander; Linz, Christian; Andersen, Peter
ABSTRACT Background In oral squamous cell carcinoma (OSCC), cervical lymph node status is the most important prognostic factor. Compared to elective neck dissection, reduced morbidity and better quality of life was demonstrated for sentinel lymph node biopsy, which is controversial because of the reduced detection rate of sentinel lymph nodes in close proximity to the injection site (also known as the shine‐through phenomenon). Methods We report the case of a 44‐year‐old woman with a biopsy‐proven early OSCC of the anterior floor of the mouth, who received SLNB guided with freehand single‐photon emission CT (fhSPECT), a system for the 3D visualization of radioactivity in the body. Results One level III sentinel lymph node and 1 level I sentinel lymph node, in close proximity to the injection site, were detected and dissected. The level I sentinel lymph node contained a metastasis. Conclusion Using fhSPECT, the issue outlined was overcome, and the precise histopathological lymph node status (pN1; 1 of 49) was determined. © 2014 Wiley Periodicals, Inc. Head Neck 36: E112–E116, 2014